Effect of honey on the reproductive system of male rat offspring exposed to prenatal restraint stress - Mohd Nizam, Haron; Mahaneem, Mohamed (2016)
Exposure to prenatal stress is associated with impaired reproductive function in male rat offspring. Honey is traditionally used by the Malays for enhancement of fertility. The aim of this study was to determine the effect of honey on reproductive system of male rat offspring exposed to prenatal restraint stress. Dams were divided into four groups (n = 10/group): control, honey, stress and honey + stress groups. Dams from honey and honey + stress groups received oral honey (1.2 g kg(-1) body weight) daily from day 1 of pregnancy, meanwhile dams from stress and honey + stress groups were subjected to restraint stress (three times per day) from day 11 of pregnancy until delivery. At 10 weeks old, each male rat offspring was mated with a regular oestrus cycle female. Male sexual behaviour and reproductive performance were evaluated. Then, male rats were euthanised for assessment on reproductive parameters. Honey supplementation during prenatal restraint stress significantly increased testis and epididymis weights as well as improved the percentages of abnormal spermatozoa and sperm motility in male rat offspring. In conclusion, this study might suggest that supplementation of honey during pregnancy seems to reduce the adverse effects of restraint stress on reproductive organs weight and sperm parameters in male rat offspring.